A FUZZY-ANALYTIC HIERARCHY PROCESS OF TOURISM SUPPLY CHAIN PERFORMANCE: CUSTOMER PERSPECTIVES - Bire, Rio Benedicto; Nugraha, Yudha Eka; Welly, Fahri Reva Adiputra (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
Evaluation of end-to-end tourism supply chain performance from the end customer (tourist) perspective is missing from literature, which necessitates for investigation. As the end customers are involved throughout all stages of the tourism supply chain, and that the tourism product is merely that of tourist experience and satisfaction, the agenda is considered quintessential. Accordingly, this research aims to investigate tourism supply chain management (TSCM) performance attributes from the tourists’ point of view. This study takes its setting in the Nusa Tenggara Timur (NTT) Province of Indonesia, a flourishing prospectus of tourism sector in the country. A Fuzzy – Analytical Hierarchy Process (F-AHP) method was employed to examine the relative importance of the criteria and sub-criteria of TSCM. Results render the stages prior to travelling as the most essential phases in the tourism supply chain that influences satisfaction in the travelling experience. Moreover, the three most critical performance criteria are visa and/or other pre-travel document arrangements cycle time, accuracy of information about the destination, and accuracy of information in the booking process. Aside from practical insights, our findings also present a foundation for further investigation into other dimensions of TSCM performance.